2013
DOI: 10.1177/0170840613483658
|View full text |Cite
|
Sign up to set email alerts
|

No Woman is Like a Man (in Academia): The Masculine Symbolic Order and the Unwanted Female Body

Abstract: Women continue to be under-represented in senior positions in universities and their relative absence from the top jobs in management and business schools remains a cause for concern. The aim of this study is to extend understanding of this situation by drawing on the feminist psychoanalytical post-structuralist theories of Luce Irigaray and Julia Kristeva. The theoretical frame proposed engages with debates over language, discourse and the body and allows development of a theory of the disembodied symbolic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
294
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(327 citation statements)
references
References 60 publications
9
294
0
6
Order By: Relevance
“…And as the meditative reflections of Heather Jeffrey's article "Gendering the Tourism Curriculum Whilst Becoming an Academic" (in this special issue) and others have shown, the increase of insecurity in the labor conditions and the expansion of the precariat do not contribute either to foster academic environments where dissenting views can be given uptake (Ayikoru, 2014;Giroux, 2014;Munar, 2016). The second way this can happen is the pervasive existence in academic work environments of discriminatory micro-aggressions and day-to-day sexism both of the paternalistic and hostile types (Ford & Harding, 2010;Fotaki, 2013). Furthermore, as explained by Daukas' (2011) analysis of virtue epistemology, people tend to be perceived as less epistemically trustworthy if they argue against the testimony or beliefsystems of certain groups, if these are perceived to be as "inferior" or having an "outsider status".…”
Section: From Marginalization To Centralitymentioning
confidence: 92%
See 1 more Smart Citation
“…And as the meditative reflections of Heather Jeffrey's article "Gendering the Tourism Curriculum Whilst Becoming an Academic" (in this special issue) and others have shown, the increase of insecurity in the labor conditions and the expansion of the precariat do not contribute either to foster academic environments where dissenting views can be given uptake (Ayikoru, 2014;Giroux, 2014;Munar, 2016). The second way this can happen is the pervasive existence in academic work environments of discriminatory micro-aggressions and day-to-day sexism both of the paternalistic and hostile types (Ford & Harding, 2010;Fotaki, 2013). Furthermore, as explained by Daukas' (2011) analysis of virtue epistemology, people tend to be perceived as less epistemically trustworthy if they argue against the testimony or beliefsystems of certain groups, if these are perceived to be as "inferior" or having an "outsider status".…”
Section: From Marginalization To Centralitymentioning
confidence: 92%
“…While the evolution of tourism research and scholarship has been studied by multiple scholars (see mapping of tourism research paradigms for a summary of this), the critical examination of the gendered epistemic and scholarly practices of our academic community has been minimal. Furthermore, as mentioned by Fotaki (2013Fotaki ( , p. 1255, "The absence of research on women's position in academia is inexplicable, especially given the numerous studies showing that organizational culture in universities is "solidly masculinized" (Leathwood & Read, 2009, p. 176)."…”
mentioning
confidence: 99%
“…Senior managers create homogeneity or diversity by legitimating or reframing hierarchies embedded in dominant organizational and societal discursive practices (Meriläinen et al 2009). For example, research in academia has shown that decisions about criteria for promotion, although seemingly gender-neutral and meritocratic, tend to favor men (Benschop and Brouns 2003, Van den Brink and Benschop 2012, Fotaki 2013. This practice reinforces a hierarchy that sustains male domination of the highest positions in academia.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…As a category, women not only had to take on these behaviors but also at the same time had to remain 'feminine. ' Fotaki (2013) has shown how this contradiction contributes to the marginalization and exclusion of women and at the same time may become common sense, forcing them to collude in this practice. The use of these discourses constructs and reproduces norms that legitimize the work habits and ideas of these heterosexual privileged men as the neutral, 'natural,' and objective managerial standard, often under the guise of meritocracy or productive logic (Janssens and Zanoni 2005).…”
Section: Constructing Women and Minoritiesmentioning
confidence: 99%
“…Sinclair 2005) of women in academia (e.g. Fotaki 2013) and extends to the writing of research in organization studies (e.g. Phillips et al 2014).…”
Section: Ecofeminist Care-sensitive Ethicsmentioning
confidence: 99%